Influence of Protein Modification and Glycosylation in the Catalytic Hydrogen Evolution Reaction of Avidin and Neutravidin: An Electrochemical Analysis - Izadi, Nasim; Černocká, Hana; Trefulka, Mojmír; Ostatná, Veronika (ChemPlusChem, 2020)
To investigate glycans' influence on the behavior of glycoproteins on charged surfaces, avidin and its nonglycosylated and neutralized version neutravidin were studied by label-free chronopotentiometric stripping (CPS) analysis and alternating current voltammetry combined with a mercury electrode. Despite neutravidin's and avidin's similar size and structure, their CPS responses differed due to the different amounts of catalytically active free amino groups of lysine and arginine residues. Acetylation of the proteins resulted in the suppression of their CPS responses by almost four times for avidin and by about 50 % for neutravidin, respectively. On the other hand, the presence of glycans in the acetylated avidin induced about 30 % higher chronopotentiometric response compared to the acetylated neutravidin. We suggest that the presence, size and composition of the glycans influenced the CPS signal due to differences in the orientation at a charged surface. The obtained results can be utilized in glycoprotein research.
Keywords: constant current chronopotentiometry; glycoproteins, glycosylation, protein modifications; electrochemical analysis